A study on geotechnical properties of marine clay stabilized with lime and recron-3s fibre - S V Prasad, D; DurgaVara Prasad, L; Shivanarayana, Ch (International Journal of Engineering and Technology, 2018)
The necessity to tap natural marine resources from the ocean beds represents a considerable challenge for the construction of offshore structures on weak marine deposits. Weak marine soil deposits have been found both on the coast and in several offshore areas spread over many parts of the world. When clay particles precipitate in salt water, there is a tendency for the clay particles to flocculate and stick together giving rise to some sort of edge-to-face arrangement. As a result, clay, silt, and fine sand particles settle almost at the same rate and the final sediment formed consists of particles with a very loose card house-like structure. In thisstudy,anattempthasbeenmadetostudytheIndex Properties, Differential Free Swell , Compactionand CBR characteristics of marine clay mixing with different percentages of lime and Recron-3s fibre with a view to determine the optimum percentages and its effect on strength characteristics.Test results show that stabilizing marine clay with lime and imparting Recron - 3s fibre enhance the strength.